Factor V Leiden Is not a Risk Factor for Arterial Vascular Disease in the Elderly: Results from the Cardiovascular Health Study - Cushman, Mary; Rosendaal, Frits R.; Psaty, Bruce M.; Cook, E. Francis; Valliere, J.; Kuller, Lewis H.; Tracy, Russell P. (Thrombosis and Haemostasis, 1998)
Coagulation factor V Leiden is a risk marker for venous thrombosis. For arterial thrombosis no large study to date has included population-based elderly patients. The Cardiovascular Health Study is a longitudinal study of 5,201 men and women over age 65. With 3.4-year follow-up, we studied 373 incident cases of myocardial infarction (MI), angina, stroke, or transient ischemic attack (TIA), and 482 controls. The odds ratios for each event with heterozygous factor V Leiden were: MI, 0.46 (95% CI 0.17 to 1.25); angina, 1.0 (95% CI 0.45 to 2.23); stroke, 0.77 (95% CI 0.35 to 1.70); TIA, 1.33 (95% CI 0.5 to 3.55); any outcome, 0.83 (95% CI 0.48 to 1.44). Adjustment for cardiovascular risk factors did not change relationships. In older adults factor V Leiden is not a risk factor for future arterial thrombosis.